Stem anatomy of Lycopersicon esculentum Mill. treated with different plant growth regulators - Martins, MBG; Castro, PRDE (Inst Tecnologia Parana, 1998)
The effects of plant growth regulators GA(3) 50 mg. L-1, NAA 100 mg. L-1, CCC 1500 mg.L-1 and SADH 3000 mg.L-1 on stem anatomy of Lycopersicon esculentum Mill cv. Angela Gigante were studied. Two sets of experiments were carried out in greenhouse during two separte periods. Anatomical studies,revealed that growth promoters induced increased xylem thickness and increased the number of tracheary elements while the growth retardants decreased xylem thickness and induced fiber formation.
Keywords: plant growth regulators; anatomy; stem; Lycopersicon esculentum